Chromosomal studies, pollen morphology and fertility in Dioscorea ayardei (Dioscoreaceae) - Asesor, Patricia N.; Andrada, Aldo R.; Páez, Valeria de los A.; Reyes, Nora J. F.; Bulacio, Eva (Instituto de Ecología, A.C., 2022)
Background and Aims: The great variability of characters in Dioscorea makes it difficult to define the species, therefore additional studies are necessary to identify them. Dioscorea ayardei, a recently described endemic species from the Sierras de Calilegua (Jujuy, Argentina), differs by the particularity of the androecium of its staminate flowers which consists of a navicular structure with a single anther in the center and three erect dendriform appendages. The aim of this paper was to carry out an ensemble study of its chromosomal and palynological characters that, added to the morphological ones, provide complementary information for its correct delimitation. Methods: The studied material was identified according to the classic methods in taxonomy and deposited in the LIL Herbarium, of the Fundación Miguel Lillo. For study of meiosis, young flower buds were randomly selected, which were fixed in Farmer for 24 hours and preserved in 70° to -4°C ethyl alcohol. For chromosome staining, 2% propionic hematoxylin was used. Fertility of pollen grains was estimated using the Mützing and DAPI techniques. For the pollen morphology description the material was processed according to the conventional techniques of acetolysis and natural pollen; photographs were taken with light microscope (LM) and scanning electron microscope (SEM). Key results: Dioscorea ayardei presented a gametophytic number n=20II. Meiotic behavior was generally regular. The techniques to estimate viability and fertility of the pollen grain revealed a value of 90-93%, respectively. The morphology showed a small (16-24 µm) to medium (25-30 µm) sized disulcate grain with microreticulate tectum. Conclusions: The basic chromosome number for the genus x=10 is reaffirmed. Dioscorea ayardei is a tetraploid with n=20, with normal meiotic behavior consistent with the potential viability of the pollen grain. The exine ornamentation and chromosome number relates with the New World II clade.